Pengaruh Penggunaan Media Sosial Terhadap Perkembangan Kemampuan Komunikasi Orang Tua dan Anak - Purba, Siti Aisyah; Lubis, Rifky Rinanda; Muhammad Bagas; Fasya, Muhammad Habib; Dzulham Fatullah; Nursapiah Harahap (GAYAKU PUBLISHER, 2024)
This research aims to determine the influence of social media use on the development of communication between parents and children, to find out whether the use of social media has a positive or negative effect on the openness of communication between parents and children, how often and for how long it influences the intensity of direct communication between the two, and how both parties view the use of social media. Research data was collected through a survey given to students at the State Islamic University of North Sumatra. The instrument used in this research was an online questionnaire given to UINSU students. The results of research regarding the frequency of use of social media show that as many as 68% fall into the “agree” category. 64% said they “agree” with the statement that the use of social media improves communication between parents and children. 61% “agree” that social media use has an impact on communication between parents and children.